Efek Ekstrak Etanol Daging Putih Semangka dan Simvastatin Terhadap Aktivasi Nuclear Factor Kappa Beta (NF- kβ) Aorta Tikus Rattus Norvegicus yang Diberi Diet Aterogenik - Manggasa, Dafrosia Darmi (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2017)
Atherogenic diet can lead to dyslipidemia condition that trigger increase Reactive Oxygen Species (ROS) and oxidative stress. The increasing of ROS can activate transcription factor Nuclear Factor Kappa Beta (NF-kβ). Activated NF-kβ induce proinflammatory cytokines that will increase the atherosclerosis progressivity. Watermelon rind had proven to have antioxidant compounds that can inhibit ROS. This study was aimed to prove the effect of watermelon rind extract and simvastatin to decrease the NF-kβ aktivation of Rattus norvegicus with atherogenic diet. This research was using Post Test Only Control Group Design. The samples were divided into five groups: (i) standard diet (K(-)), (ii) atherogenic diet (K(+)), (iii) atherogenic diet + watermelon rind extract 250 mg/kgBW/day, (iv) atherogenic diet + watermelon rind 500 mg/kgBW/day, and (v) the atherogenic diet + simvastatin 0.9 mg/kgBW/day. Atherogenic diet was given for 8 weeks. NF-kβ were measured by immunohistochemistry. Data were analyzed with ANOVA and post hoc test. The results showed a significant decrease mean NF-kβ activation after treatment of watermelon rind extract of 250 mg/kg/day (p =0,000), dose of 500 mg/kg/day (p = 0.000), and simvastatin dose of 0.9 mg/kg/day could reduced NF-kβ significantly (p = 0,000) compared with atherogenic diet group. It concluded that the watermelon rind extract dose 500 mg/kgBW/day was equivalent to simvastatin 0,9 mg/kgBW/day in lowering the NF-kβ activation rats with atherogenic diet.